Factors effecting the lactation curve parameters of Brown Swiss and Jersey cows in Türkiye - Yıldırır, M (Journal of the Hellenic Veterinary Medical Society, 2024)
The explanatory capacity of the lactation models depends on the successful prediction of the lactation process and the regulation of environmental factors affecting production parameters. Therefore, in this study, six different lactation curve models (Wood, Wilmink, Sikka, Gou and Swalve, Nelder and Cobby and Le Du) were used to compare lactation milk yield data in individual monthly interval. Yield records in the first five lactations (1-5) were used a total of 61525 lactations data belonging to 22955 Brown Swiss (BS) and 5178 Jersey (JR) cows. Except for the Cobby and LeDu curve model, the explanatory capacity for the lactation curve models of the other models was quite high and the adjusted R2 (between 0.95 and 0.99) and RSD (between 0.97 and 1.03) were found to be close to the others. Observed and estimated milk yield had higher milk yield in EU origin BS cows, while TR origins had higher milk yield in JR cows (P<0.01). Observed and estimated milk yield were higher autumn-winter season compared to the spring-summer season in both breeds (P<0.01). With this approach, Wood’s curve model was able to make a successful prediction in terms of lactation dynamics and environmental factors affecting production for both breeds. Moreover, results with sufficient accuracy were obtained with the Wood model in terms of breed-origin and environmental factors (breeding region, parity, season and year) affecting lactation processes. The factors such as year of calving, season of calving and parity were the most important factors that accounted for the large amount of the variation.